The media, protest at and nation building in post-apartheid South Africa : The spear : a case study - Makwela, Mologadi (Centre for Film and Media Studies, 2015)
This study examines the media coverage and public debate that ensued following the publication of The Spear, a painting by artist Brett Murray which depicted African National Congress (ANC) President Jacob Zuma with his genitals exposed. The objective of the study is twofold. First, to understand how the debate unfolded in media and second, to unpack the public (and ANC) reaction to the media’s reports. The study attempts of contribute to research related to the relationship between media, society and nation building in young democracies, specifically in post-apartheid South Africa. A qualitative content analysis of a purposely selected sample of online news articles and comments formed the basis of the research methodology through which to identify prevalent themes that arose throughout the debate. Through discourse analysis, the study also unpacks how social structures – by these I mean groups, institutions, the economy, laws, population dynamics and social relations – that form the national landscape are created and maintained through the use of language (Gee, 2005: 65). Afrocentricism, media framing and agenda setting, as well as social and cultural identity theories, provide theoretical constructs with which to unpack a number of important aspects inherent in the media’s representation of Jacob Zuma. The findings reveal that while the painting as a metaphor of the shortcomings of an individual was relevant, historic memory paired alongside increasing class and racial tensions in South African society, escalated what otherwise would have been a form of protest art into an issue of racism and disrespect of African/black culture.